Estrutura genética espacial e temporal de Calyptranthes clusiifolia em fragmentos no sul de Minas Gerais - Duarte, Jaqueline Fidelis (2015)
Most of the studies related to the fragmentation process focuses on the quantification of species richness, population structure and dynamics, changes in ecological processes, among others. But, because forests are being rapidly destroyed, it is necessary to investigate what are the effects of fragmentation on the point of view of genetic diversity, ensuring that the habitat conservation measures be really effective. To evaluate the effects of fragmentation on tree species it is important to take into consideration that their lifetime is often higher than the fragmentation process in a given area and, therefore, depending on the type of sampling, these effects can be hidden. Thus, using a sampling that allows embracing different generations, it can increase the chances to describe a more realistic overview of the genetic dynamics in a population. Another important point to be studied is the possibility of comparing areas with different origins, such as remaining fragments of human activities compared to naturally occurring fragments. In this study, we investigated how forest fragmentation can influence the genetic dynamics and spatial genetic structure. For this, the tree species Calyptranthes clusiifolia was sampled in two fragmented areas. Seven polymorphic microsatellite markers were developed to assess the genetic diversity of the species. In each study area, 680 individuals were collected in two different years. The genetic diversity value was lower in regenerating groups of the two areas than the sampled groups in the first year of collection, showing differences in temporal genetic dynamics. Spatial genetic structure was detected within the four groups sampled, that is, it can not be asserted that fragmentation would be influencing the non-random distribution of individuals in these areas.